The - Sadie, Stanley (St. Martin's Press, 1997)
Incorporating a decade of musicological research, the Dictionary is unsurpassed in its scope and quality, with contributions from over 1,300 of the world's leading critics and scholars. A remarkable 11,000 articles, all fully cross-referenced, create a work that has become established as the essential opera reference. Indeed, every aspect of this varied art form is covered: composers, conductors, directors, performers, librettists, literary sources, cities and countries, operatic historians, and opera genres and terminology